2019
DOI: 10.1103/physrevd.99.074513
|View full text |Cite
|
Sign up to set email alerts
|

Energy shift of the three-particle system in a finite volume

Abstract: Using the three-particle quantization condition recently obtained in the particle-dimer framework, the finite-volume energy shift of the two lowest three-particle scattering states is derived up to and including order L −6 . Furthermore, assuming that a stable dimer exists in the infinite volume, the shift for the lowest particle-dimer scattering state is obtained up to and including order L −3 . The result for the lowest three-particle state agrees with the results from the literature, and the result for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 67 publications
7
74
0
1
Order By: Relevance
“…[41,42] for a comprehensive calculation of meson-meson scattering lengths. * chrisculver@email.gwu.edu † maximmai@gwu.edu ‡ aalexan@gwu.edu § doring@gwu.edu ¶ fxlee@gwu.edu Systems of more than two pions with maximal isospin have been calculated in lattice QCD [43,44] and serve as a test ground for infinite-volume mapping techniques that are currently being developed [45][46][47][48][49][50][51][52][53][54]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[41,42] for a comprehensive calculation of meson-meson scattering lengths. * chrisculver@email.gwu.edu † maximmai@gwu.edu ‡ aalexan@gwu.edu § doring@gwu.edu ¶ fxlee@gwu.edu Systems of more than two pions with maximal isospin have been calculated in lattice QCD [43,44] and serve as a test ground for infinite-volume mapping techniques that are currently being developed [45][46][47][48][49][50][51][52][53][54]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 illustrates diagrammatically the relations given in Eqs. (20), (21), and (23). It is useful to compare Fig.…”
Section: B Hs-bhs Representationmentioning
confidence: 99%
“…Quantization conditions for three hadrons have been derived by various groups using different approaches [12][13][14][15][16][17][18][19][20][21][22][23], as recently reviewed in Ref. [24].…”
Section: Introductionmentioning
confidence: 99%
“…The first step, namely the derivation of a quantization condition, has been achieved for a relativistic system of three identical particles [135,136], including the possibility of mixing with states containing two particles [137] and resonant subprocesses [138]. Several important cross-checks of the formalism have been carried out [139][140][141][142][143][144][145]. A recent review can be found in Ref.…”
Section: Multihadron Physicsmentioning
confidence: 99%
“…[146]. A simpler form has been derived for the three-particle case using a nonrelativistic effective field theory [145,147,148], while other relativistic approaches have also been considered [149,150]. Finite-volume energies now depend not only on two-particle scattering amplitudes but also on three-to-three amplitudes.…”
Section: Multihadron Physicsmentioning
confidence: 99%